Analytic average magnetization expression for the body-centered cubic Ising lattice - Kaya, Tuncer (SPRINGER HEIDELBERG, 2022)
The average magnetization of the body-centered cubic Ising lattice is investigated by the use of the interrelation developed recently by us. We apply the same conjectures made for the odd spins correlation functions as in our previous works. The mathematical forms of the odd spin correlation functions are eventually elucidated by some physical discussions. We have seen that the obtained average magnetization expression is in good agreement with the numerical data for the body-centered cubic lattice Ising model.
Keywords: MONTE-CARLO; CRYSTAL STATISTICS; CRITICAL EXPONENTS; MODEL; RENORMALIZATION; TEMPERATURE; HONEYCOMB; FERRIMAGNETISM; CONJECTURES; SQUARE; Physics